Inter-parental conflict, parent-child relationship on emotional security of school-going adolescents in Ibadan South-West Local Government Area, Ibadan, Oyo State (2016)
The rate of loneliness, anxiety, depression, emotional distress, distrust in relationships among adolescents and their implications for student',' academic performance, relationship with teachers and peers, personality, choice of career, emotional development and preparation for life have been traced to variations in adolescents' emotional security. The foregoing has inspired investigation into inter-parental conflict and parent-child relationship as determinants of emotional security of school-going adolescents in Ibadan South-West Local Government Area of Oyo State. The study adopted the descriptive survey research design of the ex-post facto type, with a sample of 248 adolescents (between the ages of 13 and 19 years) randomly selected from junior secondary schools in Oyo State. Three measuring scales (Inter-parental conflict scale; r = 0.78, Parent-child relationship scale; r = 0.73 Emotional security scale = 0.76) were used in collecting data. Pearson's product moment correlation and multiple linear regression were used in testing three research questions at 0.05 level of significance. The result indicated that inter-parental conflict (r = -.821, P<0.01) and parent-child relationship (r =.885, P<0.01) significantly correlated with adolescents' emotional security. The regression analysis confirmed that the independent variables jointly accounted for 81.6% variance in the prediction of adolescents' emotional security. Parent-child relationship (Beta = .636, t= 14.883, P<0.01) was found to be the strongest predictor of adolescents' emotional security, followed by inter-parental conflict (Beta = .636, t= 14.883, P<0.01). By implication, reduction in inter-parental conflict will improve adolescents' emotional security, while a unit change in parent-child relationship will increase the likelihood for an improved adolescents' emotional security. It was recommended that parents should not discuss their grievances or exchange words in the presence of their children because of its effects on their emotional development. They were also enjoined not to transfer aggression to their children. School counsellors were enjoined to help adolescents develop emotional regulatory ski/Is to adjust unpleasant situations or events in life.